Xanthogranulomatous orchitis: a case series - Sambhus, Tanvi R.; Sharma, Swati; Pai, Kanthilatha; Mathew, Mary (International Journal of Research in Medical Sciences, 2023)
Xanthogranulomatous orchitis (XGO) is a sporadic disorder that has no definite aetiology and is a mimicker of several conditions, most significant of which are testicular neoplasms. We present a case series of three cases. The first case presented with swelling in his scrotum. The second case presented with similar symptoms and had prior history of trauma to the scrotum. Both cases were clinically diagnosed with testicular tumour. The third case was a referred case of left chronic orchitis with sinus tract. All three patients underwent high inguinal orchidectomy. Regardless of clinical work-up and diagnoses, upon histopathological evaluation, all three cases were diagnosed with XGO. This study explores the variety of risk factors and aetiologies that may result in XGO.